Anaerobic digestion of alkali-pretreated kitchen waste extract - Acosta, Voltaire B. (2006)
The Philippine Ecologocal Solid Waste Management Act of 2000 mandates local government units (LGUs) to divert recyclable materials and the organic fractions of municipal solid waste (OFMSW) from disposal site by segregation and bioprocessing. About 45% of MSW generated in most urban areas in the country id food and kitchen waste and many LGUs manage these using aerobic composting technologies. We propose to demonstrate the suitability of anaerobic digestion (AD) system to treat OFMSW. In this system, methane can be captured for potential use in energy generation. To enhance the process, we applied several pre-treatment of the kitchen waste: comminution, extraction and addition of sodium hydroxide to achieve the desired pH (8.0). The extract was stored an replenished every two weeks in a feed reservoir and its pH was corrected to 8.0 twice a week. The extract was continuously pumped to the up flow anaerobic sludge blanker reactor (UASB) at an organic loading rate (OLR) of 12.5 kg TCO/m3-d during a 69-day period. During the first 16 days when OLP was set at around 9.0 kg TCO/m3-d, 9.5% of the total TCOD fed was converted into methane. From days 16 to 31, OLR was increased to 12.5 kg TCOD/m3-d, which resulted in higher effluent TCOD and hampered methane generation rates. Starting day 31, OLP was reduced to 7.0 but was gradually increased to 11.1 kg TCOD/m3-d at the last feeding period. This brought about 70 to 95% TCOD removal and an increase of methane generation from 2.25 to 3.70 g CH -COD/l-d. During days 31-69, methane production from the UASB reactor increased more as compared to that coming from the storage tank. The SGP recorded during a more or less stable condition, i.e., during days 58-69, was 0.087 m3/kg-TCOD (28.9˚C, 1 atm) or 0.079 m3/kg-TCOD (0˚C, 1 atm). The GPR at day 69 was found to be 1.425 m3/m3 reactor -d (28.9˚C, 1 atm) or 1.289 m3/m3 reactor -d (0˚C, 1 atm). This GPR was relatively high as compared to other AD systems used to treat OFMSW, i.e., a relatively smaller volume of reactor would be required for the same amount of methane recovered.
Thesis (M.S. Environmental Engineering) - University of the Philippines Diliman.
Keywords: Sewage -- Purification -- Anaerobic treatment; Organic wastes -- Purification